INVESTIGATION OF PRE-SERVICE PRIMARY SCHOOL TEACHERS’ MATHEMATICS ANXIETY AND MATHEMATICS TEACHING ANXIETY - Mehmet Koray SERİN (International Journal of Eurasia Social Sciences, 2017)
The aim of this study is to determine the pre-service primary school teachers’ anxiety level for the mathematics in general and their anxiety level for teaching mathematics in the classroom as a teacher. That is, it is aimed to identify the possible level of relationship between these two variables. The research adopts the quantitative paradigm in terms of data collection and analysis, and it is designed according to the relational survey method. The participants were the third and fourth grade students who were studying in the Department of Primary School Education at the Faculty of Education in 2016-2017 academic year. Two basic data collection tools were used in this research. The first of them is the Mathematics Anxiety Scale Towards Teachers and Teacher Candidates (MAS-T), which was developed by Uldas (2005), and the other is the Mathematics Teaching Anxiety Scale (MATAS), which was developed by Peker (2006). In the data analysis, arithmetic mean (x ¯), independent samples t- test and Pearson moments correlation coefficient were used. According to the findings, it was found that the pre-service primary school teachers’ both mathematics anxieties and mathematics teaching anxieties were at low level. It has been observed that the third grade pre-service teachers had a significantly higher level of anxiety than the fourth grade pre-service teachers in both types of anxiety. Also, it was found out that there was a positively high level of relationship between the mathematics anxiety and mathematics teaching anxiety.